Common T-cell-receptor motifs and features in patients with cytomegalovirus (CMV)-seronegative end-stage renal disease receiving a peptide caccination against CMV - Bunse, Lukas; Sommerer, Claudia; Tan, Chin Leng; Korell, Felix; Schmitt, Anita; Hückelhoven-Krauss, Angela; Neuber, Brigitte; Mertens, Thomas; Platten, Michael; Green, Edward W.; Zeier, Martin; Schmitt, Michael (International journal of molecular sciences, 2022)
After solid-organ transplantation, reactivation of the cytomegalovirus (CMV) is often observed in seronegative patients and associated with a high risk of disease and mortality. CMV-specific T cells can prevent CMV reactivation. In a phase 1 trial, CMV-seronegative patients with end-stage renal disease listed for kidney transplantation were subjected to CMV phosphoprotein 65 (CMVpp65) peptide vaccination and further investigated for T-cell responses. To this end, CMV-specific CD8+ T cells were characterized by bulk T-cell-receptor (TCR) repertoire sequencing and combined single-cell RNA and TCR sequencing. In patients mounting an immune response to the vaccine, a common SYE(N)E TCR motif known to bind CMVpp65 was detected. CMV-peptide-vaccination-responder patients had TCR features distinct from those of non-responders. In a non-responder patient, a monoclonal inflammatory T-cell response was detected upon CMV reactivation. The identification of vaccine-induced CMV-reactive TCRs motifs might facilitate the development of cellular therapies for patients wait-listed for kidney transplantation.